THE IMPACT OF SOCIAL MEDIA ON POLITICAL MOBILIZATION: THEORETICAL ASPECTS. - Молдованенко, А. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the mechanisms of the effect of social media on political mobilization and also analyzes the effectiveness of such mobilization.